2013
DOI: 10.1016/j.indcrop.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of torrefaction conditions for high energy density solid biofuel from oil palm biomass and fast growing species available in Malaysia

Abstract: Without appropriate treatment, lignocellulosic biomass is not suitable to be fed into existing combustion systems because of its high moisture content, low bulk energy density and difficulties in transport, handling and storage. The aim of this study was to investigate the effects of torrefaction treatment on the weight loss and energy properties of fast growing species in Malaysia (Acacia spp., and Macaranga spp.) as well as oil palm biomass (oil palm trunk and empty fruit bunch). The lignocellulosic biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 21 publications
6
50
1
Order By: Relevance
“…The HHV significantly increased with torrefaction temperature than reaction time. This tendency is consistent with the previous work [7,9], and is mainly due to the carbon content increase meanwhile the oxygen and hydrogen decrease. This decrease in hydrogen and oxygen is due to dehydration and de-carbondioxide from the biomass during torrefaction [10].…”
Section: The Influence Of Time (A 5; B30; C55 Minutes) In Operatiosupporting
confidence: 93%
See 1 more Smart Citation
“…The HHV significantly increased with torrefaction temperature than reaction time. This tendency is consistent with the previous work [7,9], and is mainly due to the carbon content increase meanwhile the oxygen and hydrogen decrease. This decrease in hydrogen and oxygen is due to dehydration and de-carbondioxide from the biomass during torrefaction [10].…”
Section: The Influence Of Time (A 5; B30; C55 Minutes) In Operatiosupporting
confidence: 93%
“…Decreasing of hemicellulose and volatiles will increase calorific value and maximize mass yield and energy yield from solid product [5][6][7][8] Uemura et al [5] torrefied empty fruit bunch at 225-275 °C and stated that temperature played a significant role toward solid product. Chin et al [7] investigated OPT at 200-300 °C for 15-45 minutes. They found that time also affected torrefaction but was not as signifant as temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Various works have shown that the effect of torrefaction temperature has a more pronounced effect than residence time, for instance, Chin et al [28] concluded that although the GCV (MJ/kg) increased with both residence time and temperature, the value was more influenced by torrefaction temperature. In contrast, the present study has found that the overall increase in the GCV (MJ/kg) is comparable for both temperature and residence time.…”
Section: Effect Of Residence Time On Torrefaction Parametersmentioning
confidence: 99%
“…degraded and the nature of the resulting product was between that of lignocellulose and charcoal (Chin et al 2013b). Hernández-Mena et al (2014) studied the effect of slow pyrolysis on the biochar properties of bamboo (Dendrocalamus giganteus Munro).…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo torrefied under carbon dioxide atmosphere at 240 to 340 °C, obtained solid products with mass yield 41 to 97%, energy yield 63 to 99%, and HHV 18.78 to 28.51 MJ/kg (Li et al 2015a). Bamboo is extremely high in lignin content (29 to 46%), and this makes it a desirable species for solid biofuel production, as a high lignin content in the torrefied biomass results in a higher HHV (Chin et al 2013b). Co-firing with bamboo by replacing up to 30% of the coal requirements has been shown to be economical and is a promising environmentally friendly technology (Chao et al 2008).…”
Section: Introductionmentioning
confidence: 99%